Ø§ÙÙÙÙØ¬ Ø§ÙÙØÙÙ Ø¹ÙØ¯ Ø§ÙØ¨ØµØ±ÙÙÙ - Yasmadi, Yasmadi (AT-TALIM, 2015)
the aim of the study is to identify the Arabic grammar based on Nahu. Formerly, Basrah scholars focused on their study to determine Nahu and Arabic grammar. Although they agreed with Kufah group that hadits and word sayings of Arabic people can become references to in determining syntactical structure (grammar) of Arabic language. Thus, they provide strong requirement to those references. Meanwhile the scholars made qiyas as ijma` as Nahu regulations. Copyright © 2015 by Al-Talim All right reserved